BIOACTIVITY OF FRAGRANT PANDAN AND WULUH STARFRUIT COMBINATION LEAF POWDERS AGAINST THE MORTALITY OF RICE WEEVIL (Sitophilus oryzae) - Lisa, Oviana; Lizmah, Sumeinika Fitria; Sari, Putri Mustika; Aminah, Siti; mustaqim, mustaqim (JBIO: jurnal biosains (the journal of biosciences), 2023)
Storing rice for a long time in the warehouse has the potential to be attacked by warehouse pests, namely rice weevil insect (Sitophilus oryzae). Rice weevil attacked on storage rice caused a decrease in the quality and quantity of rice, so environmentally friendly pest control is needed, such as the used of bioactive plant compounds as botanical insecticides. This research aimed to see the effect of bioactive compounds from the combined powder of fragrant pandan (Pandanus amaryllifolius) and wuluh starfruit (Averrhoa bilimbi) leaves on the mortality of the rice weevil pest S. oryzae. The method of this research used a non-factorial Completely Randomized Design (CRD) experimental method with 4 concentration levels of botanical insecticide combination powder, that were 30, 40, 50 and 60 g. The research results showed that the combination of fragrant pandan and wuluh starfruit leaf powders contained bioactive compounds were steroids, terpenoids, saponins, flavonoids, phenolics and tannins. The activity of the bioactive compounds saponins, flavonoids, phenolics and tannins worked as inhibitors of insect feeding (antifeedant) and caused the mortality of S. oryzae. The highest mortality percentage reaching 85% was obtained after applicated by a concentration of 50 g. The increase in mortality of the S. oryzae pest occurred every week, until mortality reached more than 80% in the 3rd week was obtained in treatment concentrations of 30 g (84.2%) and 50 g (85%).